Investigation of the effect of equal and unequal feeding time intervals on process stability and methane yield during anaerobic digestion grass silage. (April 2022) - Egwu, Uchenna; Onyelowe, Kennedy; Tabraiz, Shamas; Johnson, Emmanuel; Mutshow, Alexander D.
Abstract: The effects of equal and unequal feeding intervals, organic loading rates (OLR) and operating temperatures on specific methane production (SMP) during the anaerobic digestion (AD) process were investigated using three pairs of continuously stirred tank reactors (CSTRs). The Pair 1, 2 and 3 CSTRs were operated at psychrophilic (25 ± 2 °C), mesophilic (40 ± 3 °C) and thermophilic (60 ± 2.5 °C) conditions, respectively. After acclimatization, the reactors were fed at an OLR of 1.0 and 1.5gVS/L.d at selected intervals, while maintaining their pH 6.8–7.2 with NH4 HCO3 solution. The results showed that during uneven feeding regime (day 8–93), the mean SMP from Pair 1, 2 and 3 reactors were 294.5, 433.5 and 370.2 N mLCH4 /gVS fed, respectively. At failing state (day 60–93), the mean concentrations of free ammonia nitrogen (FAN) in the psychrophilic, mesophilic and thermophilic CSTRs were 19.1, 33.7 and 127.2 mg/L; VFAs of 6940.1, 6852.3 and 4694.9 mg HAc/L; which reduced their SMPs to 140, 273.8 and 231.1 N mLCH4 /gVS, respectively. Therefore, uneven feeding, trace elements (TEs) deficiency, VFAs accumulation and FAN (for thermophilic) led to CSTRs failure. An even (24-hourly) feeding regime with daily biomass ash-extracts supplement enhanced the recovery of the failed CSTRs. Although, uneven daily feeding conditions led to AD process instability, it favoured SMP in mesophilic CSTRs compared to psychrophilic and thermophilic. These results strongly indicate that the soluble TEs and alkalinity contained in ash-extracts facilitated the recovery of the failed AD reactors and therefore can be used to revive failed AD processes. Highlights: Unequal daily feeding intervals increased instability of CSTRs. Daily buffering of CSTRs with NH4 HCO3 led to ammonia inhibition. SMP from Psychrophilic < Mesophilic ≤ thermophilic CSTRs. TE and buffering alkalinity of ash-extract increase stability of AD process. Ash-extracts supplements accelerate recovery of the failed CSTRs.